PENOKOHAN DALAM NOVEL YUKI GUNI KARYA KAWABATA YASUNARI KAJIAN PSIKOLOGI SASTRA - Suarmayani, Putu Ika (Humanis; Volume 4. No. 1. Juli 2013)
The main object of this research is taken from Japanese novel with the title Yuki Guni written by Kawabata Yasunari. This novel is used for research because it got a nobel prize for Japanese literature in 1968. The whole content story of this novel touches the sense of readers because it describes or illustrates psychologically the feeling of it’s figure. This research focuses on the main problem in the term of instrinsic substances such as figures, plot, background the main figure as well as the second figure in Yuki Guni’s novel use the psychology theory. This research uses literature study and data is then analyzed in structuralism theory based Teeuw and psychology theory based on Sigmund Freud. In analyzing the data, the researcher uses descriptive method then the result is presented in the form of informal method. From the facts finding if this research that the main figure whose named Shimamura is described as a man who has got married that easily fall in love with Komako and Yoko. The second figure Komako is an antagonist character as jealous girl and bad tampered. She is most of the time hates Yoko otherwise Yoko is a very kindhearted girl. Yoko never hates Komako even though Komako treats her badly as her unwisely attitude.
Keywords: Psychology literature, figures, plot and setting.